Corticoperipheral neuromuscular disconnection in obstructive sleep apnoea. Issue 1 (11th May 2020) - Gouveris, Haralampos; Bahr, Katharina; Schmitt, Elena; Abriani, Ali; Boekstegers, Tjarko; Fassnacht, Sanja; Huppertz, Tilman; Groppa, Sergiu; Muthuraman, Muthuraman
Abstract: The roles of central nervous mechanisms and cortical output in obstructive sleep apnoea remain unclear. We addressed corticomuscular coupling between cortical sensorimotor areas and lower facial motor units as a mechanistic pathway and as a possible surrogate marker of corticoperipheral motor control in obstructive sleep apnoea. In this exploratory cross-sectional retrospective study, we analysed EEG (C3 and C4 leads) and chin EMG from polysomnography recordings in 86 participants (22 females; age range: 26–81 years): 27 with mild (respiratory disturbance index = 5–15 events/h), 21 with moderate (15–30 events/h) and 23 with severe obstructive sleep apnoea (>30 events/h) and 15 control subjects (<5 events/h). By computing C3-/C4-EEG–chin EMG coherence of signal dynamics in time and frequency domains, we investigated corticomuscular coupling between cortical sensorimotor areas and lower facial motor units with increasing obstructive sleep apnoea severity during the entire sleeping time, during different sleep stages and during obstructive respiratory events, including 5 s before (stable breathing) and after events (breathing resumption). In addition, we studied a possible influence of body mass index and autonomic nervous system activation. We found that both average and respiratory event-specific corticomuscular coupling between cortical sensorimotor areas and lower facial motor units weakened significantly with increasing obstructive sleep apnoea severity, was strongest during N3 and weakened in N1, N2 and rapid eye movement stages (in decreasing order). Coupling increases significantly during the obstructive respiratory events compared with coupling just before and following them. Results were independent of body mass index or autonomic nervous system activation. We conclude that obstructive respiratory events in obstructive sleep apnoea are very strongly associated both quantitatively and temporally with the degree of disconnection within the cortical sensorimotor areas—lower facial motor units pathway. This quite coordinated activity pattern suggests a cortical sensorimotor area-driven obstructive respiratory event pattern generator and a central motor output disorder in obstructive sleep apnoea. Abstract : In patients with obstructive sleep apnoea, corticoperipheral coupling between cortical sensorimotor areas and lower facial motor units weakens significantly with increasing obstructive sleep apnoea severity; while strongest during N3, it weakens in N1, N2 and rapid eye movement stages. Coupling increases significantly during obstructive respiratory events compared with coupling just before and following them. Graphical Abstract: